Global changes in the development of the export potential of the grain sub-complex of the agrarian sector of Ukraine - Kyrylov, Yurii; Ibatullin, Marat; Konovalenko, Anastasiia; Коноваленко, Анастасія Сергіївна; Shylo, Zhanna; Pochernina, Nataliia; Почерніна, Наталя Вікторівна (My University, 2024)
In modern conditions, the export of agricultural products is one of the main sources of income for the agricultural sector of Ukraine. Thus, conducting multi-faceted studies of foreign trade in this sector is relevant. The purpose of the study was to develop estimates of the possibility of developing grain exports in Ukraine based on the analysis of current data on the development of this sector, and individual global trends. The paper investigated global changes in the development of the export potential of the grain and food sub-complex of the agricultural sector of Ukraine. It is proved that the decomposition of the export potential of the grain sub-complex according to the sectoral system of the agrarian sector allows forming a step-by-step methodical assessment of its quantitative and qualitative indicators to determine the compositional integrity of the effective value of the object under study. A comprehensive functional-resource analysis of the parameters of the export potential of the grain sub-complex, which are grouped according to the process approach for calculating the food security of the export chain of grain production entities, is presented. The procedure for assessing the state of food security of the grain sub-complex of the state through the resource component allows diagnosing the export capabilities of subjects of foreign trade operations in the presence of numerous risks. The actual dependence of the gross domestic product of Ukraine on the export of products of the grain sub-complex was determined and its forecast value for a five-year period was calculated.
Keywords: industry system; military invasion impacts; war period trends; market integration difficulties; international trade